Low-reaction-threshold rare earth modified medium-entropy alloy and preparation method thereof

By introducing rare earth element Ce into TiZrTa medium entropy alloy and adopting vacuum high-frequency induction smelting technology, the problems of high reaction threshold and insufficient energy release rate of the medium entropy alloy are solved, and a lower reaction threshold and higher energy release rate are achieved, which improves its damage power under high-speed impact.

CN119776712AActive Publication Date: 2025-04-08CHINA WEAPON SCI ACADEMY NINGBO BRANCH

Patent Information

Application Number
CN202411982330.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-04
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The reaction threshold of medium-entropy alloys is high under high-speed impact, resulting in insufficient energy release rate, making it difficult to fully stimulate their energy release reaction, and there is a waste of chemical energy.

Method used

The rare earth element Ce is introduced into the TiZrTa medium-entropy alloy, and the uniform distribution of rare earth elements is achieved through vacuum high-frequency induction smelting technology, reducing the reaction threshold of the medium-entropy alloy and improving the energy release rate.

Benefits of technology

The reaction threshold of the medium-entropy alloy is significantly reduced, its application scenarios are broadened, and the continuous combustion energy release of the active components of the medium-entropy alloy is achieved through the ultra-long combustion time of rare earth elements, which significantly improves the energy release rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776712A_ABST
    Figure CN119776712A_ABST
Patent Text Reader

Abstract

The invention relates to a rare earth modified medium-entropy alloy with a low reaction threshold value, which is characterized in that the rare earth modified medium-entropy alloy with the low reaction threshold value is a TiZrTa medium-entropy alloy, and the adopted rare earth is an element Ce. The invention further discloses a preparation method of the rare earth modified medium-entropy alloy. By adopting vacuum sintering and vacuum high-frequency induction melting, the obtained alloy has high strength, good plasticity, excellent energy release characteristic and lower reaction threshold, and has potential application value in energetic structure materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a TiZrTa medium entropy alloy, which is applied to high-efficiency destructive weapons and a method for preparing the medium entropy alloy. Background Art

[0002] Energetic structural materials are a new type of structural and functional integrated materials for future high-efficiency destructive weapons. They have high structural stability under normal conditions, but under high-speed impact loads, they will reach the plastic deformation limit and break into tiny metal destructive elements. In addition to kinetic penetration, these metal destructive elements can also undergo self-reactions between components or oxidation reactions between components and the environment, releasing a large amount of chemical energy and producing intense combustion or even quasi-detonation phenomena, thereby achieving an ideal destructive mode of dual coupling of mechanical damage and chemical damage. Replacing the inert components in existing warheads with energetic structural materials will give the warheads a unique destructive effect and promote a leap-forward improvement in the destructive power of the warheads.

[0003] Entropy-controlled alloys represented by medium-entropy alloys have high energy density, high strength and good plastic deformation ability, and have potential application value in the field of energetic structural materials. However, the excellent strength and toughness also restrict the crushing behavior of medium-entropy alloys under high-speed impact, resulting in a high reaction threshold of medium-entropy alloys. According to existing data, the speed threshold for significant energy release of medium-entropy alloys is usually above 1200m / s, while the terminal velocity of current fragment damage elements is usually less than 1000m / s, which makes it difficult to fully stimulate the energy release reaction of medium-entropy alloys. In addition, the energy release rate of medium-entropy alloys under high-speed impact is generally less than 15%, resulting in a large amount of chemical energy waste.

[0004] Rare earth elements have active chemical properties, low ignition temperature, long combustion time and other performance characteristics, and are widely used as combustion materials. How to use rare earth elements to improve the performance of medium entropy alloys has always been a research hotspot. Summary of the invention

[0005] The first technical problem to be solved by the present invention is to provide a low reaction threshold rare earth modified medium entropy alloy in which rare earth elements are introduced into the medium entropy alloy to improve the reaction threshold and energy release rate of the entropy alloy.

[0006] The second technical problem to be solved by the present invention is to provide a method for preparing a low reaction threshold rare earth modified medium entropy alloy by introducing rare earth elements into the medium entropy alloy to improve the reaction threshold and energy release rate of the entropy alloy in response to the above-mentioned technical status quo.

[0007] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a low reaction threshold rare earth modified medium entropy alloy, characterized in that the low reaction threshold rare earth modified medium entropy alloy is a TiZrTa medium entropy alloy, and the rare earth used is the element Ce; the medium entropy alloy includes the following components and their molar ratios:

[0008]

[0009] Preferably, the medium entropy alloy comprises the following components and their molar ratios:

[0010]

[0011] As the best, the medium entropy alloy includes the following components and their molar ratios:

[0012]

[0013] The technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing a low reaction threshold rare earth modified medium entropy alloy, characterized by comprising the following steps:

[0014] ① Weigh Ti, Zr and Ta raw material powders according to the designed ratio, place them in a ball mill and mix them evenly to obtain TiZrTa mixed powder;

[0015] ② Fill the evenly mixed TiZrTa mixed powder into the container and compact it;

[0016] ③ Pre-alloying the compacted TiZrTa mixed powder by vacuum sintering to obtain a TiZrTa alloy block;

[0017] ④ Weigh the bulk rare earth Ce according to the designed ratio, put the Ce and TiZrTa alloy blocks into a crucible for vacuum high-frequency induction melting to obtain the product.

[0018] Preferably, the particle size of the Ti powder in step ① is 10-60 μm, and the purity is ≥99.95%.

[0019] Preferably, the Zr powder in step ① has a particle size of 45 to 74 μm and a purity of ≥99.95%.

[0020] Preferably, the particle size of the Ta powder in step ① is 30-50 μm, and the purity is ≥99.95%.

[0021] Preferably, the ball milling conditions in step ① are as follows: ball milling speed 80-150 rpm, ball-to-material ratio 1:2-2:1, ball milling time 4-6 h, and the process is carried out under inert atmosphere protection.

[0022] Preferably, the vacuum sintering conditions in step ③ are as follows: sintering temperature 1000-1300° C., holding time 1-3 h, vacuum degree ≤10 Pa.

[0023] Preferably, in step ④, the purity of the bulk rare earth Ce is ≥99.9%.

[0024] Preferably, the vacuum high-frequency induction melting conditions in step ④ are as follows: vacuum degree ≤ 10Pa, heating power 15-25kW, melting time 2-5min.

[0025] Compared with the prior art, the advantages of the present invention are:

[0026] This paper introduces the rare earth element Ce into the TiZrTa medium-entropy alloy. The rare earth element reacts first at a relatively low speed to release heat and ignite the active components (Ti, Zr, Ta) of the TiZrTa medium-entropy alloy, thereby significantly reducing the reaction threshold of the TiZrTa medium-entropy alloy and broadening the application scenarios of medium-entropy alloy energetic structural materials.

[0027] Driven by the ultra-long combustion time of rare earth elements, the continuous combustion and energy release of the active components (Ti, Zr, Ta) of the TiZrTa medium-entropy alloy can be achieved, which can significantly improve the energy release rate of the TiZrTa medium-entropy alloy and effectively enhance the destructive power of the medium-entropy alloy energetic structural materials.

[0028] TiZrTa mixed powder does not need to be cold pressed into a green compact, but can be sintered after vibration compaction, thus avoiding the delamination and cracking of the green compact during the cold pressing and demolding process. Pre-alloying of TiZrTa alloys through vacuum sintering helps to avoid casting defects and component volatilization caused by large differences in component melting points during the smelting process. Uniform distribution and densification of rare earth elements in TiZrTa alloys are achieved through vacuum high-frequency induction melting, which is a simple process suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the X-ray diffraction pattern of the rare earth modified TiZrTa-Ce0.4 medium entropy alloy in Example 1.

[0030] Figure 2 This is the SEM morphology of the rare earth modified TiZrTa-Ce0.4 medium entropy alloy in Example 1.

[0031] Figure 3 This is a diagram showing the ignition effect of the rare earth modified TiZrTa-Ce0.4 medium entropy alloy in Example 1 after it hits the aviation kerosene tank at 1000m / s.

[0032] Figure 4 This is the X-ray diffraction pattern of the TiZrTa medium entropy alloy in Comparative Example 1.

[0033] Figure 5 This is the SEM morphology of the TiZrTa medium entropy alloy in Comparative Example 1.

[0034] Figure 6 This is a diagram showing the ignition effect of the TiZrTa medium entropy alloy in Comparative Example 1 after it hits the aviation kerosene tank at 1000m / s. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below with reference to the accompanying drawings.

[0036] The following is a further explanation of the present invention, but not a limitation of the present invention. The described embodiments are only a part of the embodiments of the present invention, but not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In the following embodiments:

[0038] The purity of metal elements Ti, Zr, Ta and rare earth element Ce is greater than 99.9%, the particle size of Ti powder is 10-60μm, the particle size of Zr powder is 45-74μm, and the particle size of Ta powder is 30-50μm. First, a uniform TiZrTa mixed powder is obtained by ball milling process, the ball milling speed is 80-150rpm, the ball-to-material ratio is 1:2-2:1, and the ball milling time is 4-6h; secondly, the powder is filled into a container and vibrated and pre-alloyed by vacuum sintering, the sintering temperature is 1000-1300℃, the insulation time is 1-3h, and the vacuum degree is ≤10Pa; finally, the pre-alloyed TiZrTa alloy block and the Ce block are filled into a crucible, and a rare earth modified TiZrTa medium entropy alloy with a low reaction threshold is obtained by high-frequency induction melting, the vacuum degree of high-frequency induction melting is ≤10Pa, the heating power is 15-25kW, and the melting time is 2-5min.

[0039] Example 1

[0040] S1: Weigh 149.6 g Ti powder, 285.0 g Zr powder, and 565.4 g Ta powder in a molar ratio of 1:1:1, and place them in a ball mill;

[0041] S2: Add 500g of stainless steel grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder, Ta powder) of 1:2;

[0042] S3: ball milling for 4 h under inert atmosphere protection at a ball milling speed of 100 rpm to obtain uniform TiZrTa mixed powder;

[0043] S4: the TiZrTa mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for pre-alloying at a sintering temperature of 1100°C for 2 hours, and a TiZrTa alloy block is obtained after furnace cooling;

[0044] S5: Weigh 175.1 g of rare earth Ce block according to the proportion, put it into a melting crucible together with the TiZrTa alloy block, and use high-frequency induction melting equipment to melt it, with a heating power of 24 kW and a melting time of 2 minutes. The rare earth modified TiZrTa-Ce is obtained after the furnace is cooled to room temperature. 0.4 Medium entropy alloy.

[0045] The rare earth modified TiZrTa-Ce obtained in Example 1 0.4 The medium entropy alloy was tested by X-ray diffraction, SEM and gun firing to ignite aviation kerosene. The results are as follows:

[0046] Figure 1 This is the X-ray diffraction pattern of the rare earth modified TiZrTa medium entropy alloy obtained in Example 1 of the present invention. According to the spectrum, the main phase of the alloy is a BCC phase, and there are diffraction peaks of a small amount of rare earth Ce and CeO, indicating that the introduction of Ce does not change the original phase composition of the TiZrTa medium entropy alloy.

[0047] Figure 2 This is a SEM morphology of the rare earth modified TiZrTa medium entropy alloy obtained in Example 1 of the present invention, wherein the solid solution phase of the BCC structure constitutes the alloy matrix, and the rare earth Ce is dispersed therein.

[0048] Figure 3 This is a photograph of the ignition effect of the rare earth modified TiZrTa medium entropy alloy obtained in Example 1 of the present invention on aviation kerosene at 1000m / s. The rare earth modified TiZrTa medium entropy alloy effectively penetrates the 6mm thick front steel plate, and then breaks into small fragments and shoots into the fuel tank, achieving the ignition of aviation kerosene. The flame is obvious and the reaction lasts for more than 200ms, showing excellent energy release characteristics.

[0049] Comparative Example 1

[0050] S1: Weigh 149.6 g Ti powder, 285.0 g Zr powder, and 565.4 g Ta powder in a molar ratio of 1:1:1, and place them in a ball mill;

[0051] S2: Add 500g of stainless steel grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder, Ta powder) of 1:2;

[0052] S3: ball milling for 5 h under inert atmosphere protection at a ball milling speed of 100 rpm to obtain a uniform TiZrTa mixed powder;

[0053] S4: the TiZrTa mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for pre-alloying at a sintering temperature of 1100°C for 2 hours, and a TiZrTa alloy block is obtained after furnace cooling;

[0054] S5: Put the TiZrTa alloy block into a melting crucible and use high-frequency induction melting equipment for melting. The heating power is 24 kW and the melting time is 2 min. The furnace is cooled to room temperature to obtain a dense TiZrTa medium-entropy alloy.

[0055] Figure 4 This is the X-ray diffraction spectrum of the TiZrTa medium entropy alloy obtained in Comparative Example 1 of the present invention. According to the spectrum, it can be seen that the alloy has a single-phase BCC structure.

[0056] Figure 5 This is a SEM morphology image of the TiZrTa medium entropy alloy obtained in Comparative Example 1 of the present invention. The alloy cross-section contrast is uniform as a whole, with only a small amount of component segregation.

[0057] Figure 6 This is a diagram showing the ignition effect of the TiZrTa medium-entropy alloy obtained in comparative example 1 of the present invention on aviation kerosene at 1000 m / s. The TiZrTa medium-entropy alloy effectively penetrates the 6 mm thick front steel plate, and the flame duration is 20 ms, but the effective ignition of aviation kerosene is not achieved. The comparison confirms that the TiZrTa medium-entropy alloy has a lower reaction threshold and more excellent energy release characteristics after the introduction of rare earth.

[0058] Example 2

[0059] S1: Weigh 260.2 g of Ti powder, 248.0 g of Zr powder, and 491.8 g of Ta powder in a molar ratio of 2:1:1, and place them in a ball mill;

[0060] S2: Add 500g of grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder and Ta powder) of 1:2;

[0061] S3: ball milling for 5 h under inert atmosphere protection at a ball milling speed of 100 rpm to obtain a uniformly mixed TiZrTa mixed powder;

[0062] S4: the TiZrTa mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for pre-alloying at a sintering temperature of 1100°C for 2 hours, and a Ti2ZrTa alloy block is obtained after furnace cooling;

[0063] S5: Weigh 152.3 g of rare earth Ce block according to the proportion, put it into a melting crucible together with the Ti2ZrTa alloy block, and use high-frequency induction melting equipment to melt it, with a heating power of 24 kW and a melting time of 2 minutes. The rare earth modified Ti2ZrTa-Ce is obtained after the furnace is cooled to room temperature.0.4 Medium entropy alloy.

[0064] The rare earth modified Ti2ZrTa-Ce obtained in Example 2 0.4 The medium entropy alloy was tested by X-ray diffraction, SEM and gun firing to ignite aviation kerosene. The results showed that rare earth modified Ti2ZrTa-Ce 0.4 The main phase of the medium entropy alloy is BCC phase, with a small amount of rare earth Ce and CeO; SEM images show that rare earth modified Ti2ZrTa-Ce 0.4 The matrix phase of the medium entropy alloy is a solid solution phase of BCC structure, in which the rare earth Ce is dispersed; the gun firing experiment confirms that the rare earth modified Ti2ZrTa-Ce obtained in Example 2 0.4 The medium-entropy alloy can effectively penetrate the 6mm thick front steel plate at a speed of 800m / s, and at the same time achieve the ignition of aviation kerosene. The flame is obvious, the reaction lasts for more than 250ms, and the energy release characteristics are excellent.

[0065] Example 3

[0066] S1: Weigh 260.2 g of Ti powder, 248.0 g of Zr powder, and 491.8 g of Ta powder in a molar ratio of 2:1:1, and place them in a ball mill;

[0067] S2: Add 500g of grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder and Ta powder) of 1:2;

[0068] S3: ball milling for 5 h under inert atmosphere protection at a ball milling speed of 100 rpm to obtain a uniformly mixed TiZrTa mixed powder;

[0069] S4: The TiZrTa mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for pre-alloying at a sintering temperature of 1200°C for 1.5 h. After the furnace is cooled, a Ti2ZrTa alloy block is obtained;

[0070] S5: Weigh 76.2 g of rare earth Ce block according to the proportion, put it into a melting crucible together with the Ti2ZrTa alloy block, and use high-frequency induction melting equipment to melt it, with a heating power of 20 kW and a melting time of 3 minutes. The rare earth modified Ti2ZrTa-Ce is obtained after the furnace is cooled to room temperature. 0.2 Medium entropy alloy.

[0071] The rare earth modified Ti2ZrTa-Ce obtained in Example 3 0.2 The medium entropy alloy was tested by X-ray diffraction, SEM and gun firing to ignite aviation kerosene. The results showed that rare earth modified Ti2ZrTa-Ce 0.2The main phase of the medium entropy alloy is BCC phase, with a small amount of rare earth Ce and CeO; SEM images show that rare earth modified Ti2ZrTa-Ce 0.2 The matrix phase of the medium entropy alloy is a solid solution phase of BCC structure, in which the rare earth Ce is dispersed; the gun firing experiment confirms that the rare earth modified Ti2ZrTa-Ce obtained in Example 3 0.2 The medium-entropy alloy can effectively penetrate a 6mm thick front steel plate at a speed of 800m / s, and at the same time achieve the ignition of aviation kerosene. The flame is obvious, the reaction lasts for more than 200ms, and the energy release characteristics are excellent.

[0072] Example 4

[0073] S1: Weigh 149.6 g Ti powder, 285.0 g Zr powder, and 565.4 g Ta powder in a molar ratio of 1:1:1, and place them in a ball mill;

[0074] S2: Add 500g of grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder and Ta powder) of 1:2;

[0075] S3: ball milling for 5 h under inert atmosphere protection at a ball milling speed of 100 rpm to obtain a uniformly mixed TiZrTa mixed powder;

[0076] S4: the TiZrTa mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for pre-alloying, the sintering temperature is 1300°C, the holding time is 1h, and the TiZrTa alloy block is obtained after the furnace is cooled;

[0077] S5: Weigh 218.9 g of rare earth Ce block according to the proportion, put it into a melting crucible together with the TiZrTa alloy block, and use high-frequency induction melting equipment to melt it, with a heating power of 15 kW and a melting time of 5 min. The rare earth modified TiZrTa-Ce is obtained after the furnace is cooled to room temperature. 0.5 Medium entropy alloy.

[0078] The rare earth modified TiZrTa-Ce obtained in Example 4 0.5 The medium entropy alloy was tested by X-ray diffraction, SEM and gun firing to ignite aviation kerosene. The results showed that rare earth modified TiZrTa-Ce 0.5 The main phase of the medium entropy alloy is BCC, with a small amount of rare earth Ce and CeO; SEM images show that rare earth modified TiZrTa-Ce 0.5 The matrix phase of the medium entropy alloy is a single-phase BCC structure, which is consistent with the XRD analysis results. At the same time, the rare earth Ce is dispersed in it; the gun firing experiment confirms that the rare earth modified TiZrTa-Ce obtained in Example 4 0.5The medium-entropy alloy can effectively penetrate a 6mm thick front steel plate at a speed of 800m / s, and at the same time achieve the ignition of aviation kerosene. The flame is obvious, the reaction lasts for more than 200ms, and the energy release characteristics are excellent.

[0079] Example 5

[0080] S1: Weigh 208.5 g of Ti powder, 397.4 g of Zr powder, and 394.1 g of Ta powder in a molar ratio of 1:1:0.5, and place them in a ball mill;

[0081] S2: Add 500g of grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder and Ta powder) of 1:2;

[0082] S3: ball milling for 4 h under inert atmosphere protection at a ball milling speed of 150 rpm to obtain a uniformly mixed TiZrTa mixed powder;

[0083] S4: The TiZrTa mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for pre-alloying. The sintering temperature is 1100°C and the holding time is 2h. After the furnace is cooled, TiZrTa is obtained. 0.5 Alloy block;

[0084] S5: Weigh 122.1g of rare earth Ce block and TiZrTa 0.5 The alloy blocks are placed in a melting crucible and melted by high-frequency induction melting equipment with a heating power of 24 kW and a melting time of 2 minutes. The rare earth modified TiZrTa is obtained after the furnace is cooled to room temperature. 0.5 -Ce 0.2 Medium entropy alloy.

[0085] The rare earth modified TiZrTa obtained in Example 5 0.5 -Ce 0.2 The medium entropy alloy was tested by X-ray diffraction, SEM and gun firing to ignite aviation kerosene. The results showed that rare earth modified TiZrTa 0.5 -Ce 0.2 The main phase of the medium entropy alloy is BCC+HCP, with a small amount of rare earth Ce and CeO; SEM images show that rare earth modified TiZrTa 0.5 -Ce 0.2 The matrix phase of the medium entropy alloy is a dual-phase structure of BCC+HCP, in which the rare earth Ce is dispersed; the gun firing experiment confirms that the rare earth modified TiZrTa obtained in Example 5 0.5 -Ce 0.2 The medium-entropy alloy can effectively penetrate a 6mm thick front steel plate at a speed of 800m / s, and at the same time achieve the ignition of aviation kerosene. The flame is obvious, the reaction lasts for more than 200ms, and the energy release characteristics are excellent.

[0086] Example 6

[0087] S1: Weigh 116.4 g Ti powder, 443.6 g Zr powder, and 440.0 g Ta powder in a molar ratio of 1:2:1, and place them in a ball mill;

[0088] S2: Add 500g of grinding balls according to the ratio of the mass of grinding balls to the total mass of raw material powder (including Ti powder, Zr powder and Ta powder) of 1:2;

[0089] S3: ball milling for 5 h under inert atmosphere protection at a ball milling speed of 100 rpm to obtain a uniformly mixed TiZrTa mixed powder;

[0090] S4: the TiZrTa mixed powder is filled into an alumina crucible and vibrated, and then placed in a vacuum sintering furnace for pre-alloying at a sintering temperature of 1100°C for 2 hours, and a TiZr2Ta alloy block is obtained after furnace cooling;

[0091] S5: Weigh 68.1 g of rare earth Ce block according to the proportion, put it into a melting crucible together with the TiZr2Ta alloy block, and use high-frequency induction melting equipment to melt it, with a heating power of 24 kW and a melting time of 2 minutes. The rare earth modified TiZr2Ta-Ce is obtained after the furnace is cooled to room temperature. 0.2 Medium entropy alloy.

[0092] The rare earth modified TiZr2Ta-Ce obtained in Example 6 0.2 The medium entropy alloy was tested by X-ray diffraction, SEM and gun firing to ignite aviation kerosene. The results showed that rare earth modified TiZr2Ta-Ce 0.2 The main phase of the medium entropy alloy is BCC, with a small amount of rare earth Ce and CeO; SEM images show that rare earth modified TiZr2Ta-Ce 0.2 The matrix phase of the medium entropy alloy is a BCC phase, in which the rare earth Ce is dispersed; the gun firing experiment confirms that the rare earth modified TiZr2Ta-Ce obtained in Example 6 0.2 The medium-entropy alloy can effectively penetrate the 6mm thick front steel plate at a speed of 900m / s, and at the same time achieve the ignition of aviation kerosene. The flame is obvious, the reaction lasts for more than 150ms, and the energy release characteristics are excellent.

Claims

1. A low reaction threshold rare earth modified medium entropy alloy, characterized in that The low reaction threshold rare earth modified medium entropy alloy is a TiZrTa medium entropy alloy, and the rare earth used is the element Ce; the entropy alloy includes the following components and their molar ratios:

2. The low reaction threshold rare earth modified medium entropy alloy according to claim 1, characterized in that The entropy alloy includes the following components and their molar ratios:

3. The low reaction threshold rare earth modified medium entropy alloy according to claim 2, characterized in that The entropy alloy includes the following components and their molar ratios:

4. A method for preparing a low reaction threshold rare earth modified medium entropy alloy as claimed in any one of claims 1 to 3, characterized in that The steps include: ① Weigh Ti, Zr and Ta raw material powders according to the designed ratio, place them in a ball mill and mix them evenly to obtain TiZrTa mixed powder; ② Fill the evenly mixed TiZrTa mixed powder into the container and compact it; ③ Pre-alloying the compacted TiZrTa mixed powder by vacuum sintering to obtain a TiZrTa alloy block; ④ Weigh the bulk rare earth Ce according to the designed ratio, put the Ce and TiZrTa alloy blocks into a crucible for vacuum high-frequency induction melting to obtain the product.

5. The preparation method according to claim 4, characterized in that The particle size of the Ti powder in step ① is 10-60 μm, and the purity is ≥99.95%.

6. The preparation method according to claim 4, characterized in that The Zr powder in step ① has a particle size of 45 to 74 μm and a purity of ≥99.95%.

7. The preparation method according to claim 4, characterized in that The particle size of the Ta powder in step ① is 30-50 μm, and the purity is ≥99.95%.

8. The preparation method according to claim 4, characterized in that The ball milling conditions in step ① are as follows: ball milling speed 80-150 rpm, ball-to-material ratio 1:2-2:1, ball milling time 4-6 h, and carried out under inert atmosphere protection.

9. The preparation method according to claim 4, characterized in that The vacuum sintering conditions in step ③ are as follows: sintering temperature 1000-1300° C., holding time 1-3 h, vacuum degree ≤10 Pa.

10. The preparation method according to claim 4, characterized in that In step ④, the purity of bulk rare earth Ce is ≥99.9%.

11. The preparation method according to claim 4, characterized in that In step ④, the vacuum high-frequency induction melting conditions are as follows: vacuum degree ≤ 10Pa, heating power 15-25kW, and melting time 2-5min.

Citation Information

Patent Citations

  • HfZrTiTax high-entropy alloy, and preparation method and application thereof

    CN106636845A

  • Low-density Ti-Zr-Ta medium-entropy alloy and application thereof in energetic structure material

    CN113337766A

  • Ignition flame damage element material as well as preparation method and application thereof

    CN117965956A

Cited By

  • High-room-temperature plasticity TiZrTa refractory medium-entropy alloy and preparation method thereof

    CN120738536A

  • Grain refinement and ignition performance collaborative optimization preparation method of rare earth sparking alloy

    CN121491353A